TESS giants transiting giants: VII. A hot Saturn orbiting an oscillating red giant star - Saunders, Nicholas; Grunblatt, Samuel K.; Huber, Daniel; Ong, J. M. Joel; Schlaufman, Kevin C.; Hey, Daniel; Li, Yaguang; Butler, R. P.; Crane, Jeffrey D.; Shectman, Steve; Teske, Johanna K.; Quinn, Samuel N.; et al. (The astronomical journal, 2025)
We present the discovery of TOI-7041 b (TIC 201175570b), a hot Saturn transiting a red giant star with measurable stellar oscillations. We observe solar-like oscillations in TOI-7041 with a frequency of maximum power of 218.50±2.23 μHz and a large frequency separation of Δν = 16.5282±0.0186 μHz. Our asteroseismic analysis indicates that TOI-7041 has a mass of 1.07±0.05(stat)±0.02(sys) M⊙ and a radius of 4.10 ± 0.06(stat)±0.05(sys) R⊙, making it one of the largest stars around which a transiting planet has been discovered with the Transiting Exoplanet Survey Satellite (TESS), and the mission's first oscillating red giant with a transiting planet. TOI-7041 b has an orbital period of 9.691±0.006 days and a low eccentricity of e = 0.04 ± 0.04. We measure a planet radius of 1.02 ± 0.03 RJup with TESS photometry, and a planet mass of 0.36±0.16 MJup (114±51 M⊕) with ground-based radial velocity measurements. TOI-7041 b appears less inflated than similar systems receiving equivalent incident flux, and its circular orbit indicates that it is not undergoing tidal heating due to circularization. The asteroseismic analysis of the host star provides some of the tightest constraints on the stellar properties of a TESS planet host and enables precise characterization of the hot Saturn. This system joins a small number of TESS-discovered exoplanets orbiting stars that exhibit clear stellar oscillations and indicates that extended TESS observations of evolved stars will similarly provide a path to improved exoplanet characterization.